EXPLAINING PARTIAL PRIVATIZATION OF PUBLIC SERVICE PROVISION: THE EMERGENCE OF MIXED OWNERSHIP WATER FIRMS IN ITALY (1994–2009). (March 2014) - ASQUER, A.; Marra, A.; Cruz, N.F.; Fecher, F.; Marques, R.C.
ABSTRACT Within the area of study of privatization, some attention has been placed on the emergence of mixed public‐private ownership firms for the provision of public services. Mixed ownership firms pose an important theoretical issue, i.e., why do governments open up part of their ownership of public service providers to private operators and investors rather than giving up full ownership of public service providers or establishing a contractual relationship with the private partner? This paper aims to address this issue by analyzing the case of the emergence of mixed ownership firms for the provision of water services in Italy. The analysis of the case shows that partial privatization of public service providers is especially related to characteristics of the historical and institutional context as well as to features of the privatization policy process.